Aplicação de coberturas biopoliméricas de fécula de mandioca e sorbitol em queijos coalho armazenados em refrigeração - Rabelo, José Lucas Girão (Universidade Federal Rural do Semi-Árido, 2019)
Biopolymeric covers have emerged as an alternative to plastic packaging for use in food preservation due to their biodegradable properties and because they come from renewable sources, different from petroleum derivatives. Foods of animal origin, especially lactic derivatives have characteristics that make them susceptible to the development of microorganisms that can cause changes in organoleptic characteristics and still use it as a source of disease transmission. Because of this, this work aimed to evaluate cassava starch and sorbitol biopolymeric coatings on microbiological parameters of rennet cheese. The experiment was carried out by the analysis of qualitative parameters of curd cheese samples coated with different concentrations of 2% (F2) and 3% (F3) starch, the analyzes were performed on days 0, 3 and 6 for a period of six days. where aerobic mesophilic microorganisms, molds and yeasts, total and thermotolerant coliforms and positive coagulase Staphylococcus were analyzed, the cheeses used for the analyzes were coated with 2 and 3% cassava starch filmogenic solution using plasticizer. (sorbitol) to an amount of 20% of the dry extract, where all steps were performed following hygienic-sanitary standards under aseptic and sterile conditions. Among the results for the microbiological analyzes the control groups (C1), F2 and F3 had satisfactory values ranging from <3.0 MPN / g to 3.6 MPN / g, all samples were negative for thermotolerant coliforms. In the mesophyll analyzes, the values ranged from 7.19 to 8.49 log10 CFU / g for the control group (C1), 5.20 to 8.24 log10 CFU / g for the treatment with 2% cassava starch ( F2), 5.76 to 6.84 log10 CFU / g for the 3% starch group (F3), group F2 showed a reduction of almost 3.00 log10 CFU / g on the sixth day of analysis when compared to the group control. In the analysis of mold and yeast, no reduction in microbial load was found, with values ranging from 7.14 log10 CFU / g to 7.59 log10 CFU / g for group C1, 6.58 log10 CFU to 7.43 log10 CFU / g for group F2 and 6.51 log10 CFU / g 7.08 log10 CFU / g for group F3. Coagulase positive Staphylococcus results ranged from 6.06 to 8.03 log10 CFU / g for control group C1, 5.85 to 7.28 log10 CFU / g for 2% (F2) and 0.00 to 6, 69 log10 CFU / g to 3% (F3), with the F3 group showing the best results on the sixth day, causing a total inhibition in the development of staphylococci. Thus, it can be concluded that the starch coating provided antimicrobial effect against some groups of microorganisms in rennet cheese possibly due to the formation of a modified atmosphere, reducing values of mesophilic aerobic bacteria and Staphylococcus spp. that help to reduce spoilage processes and possible cases of food poisoning.
Monografia
Keywords: Conservação; Plastificante; Coberturas comestíveis; Tecnologia de alimentos; Conservation; Plasticizer; Edible coverages; Food technology; CIENCIAS BIOLOGICAS::BIOTECNOLOGIA